Ru4+ induced colossal magnetoimpedance in Ru doped perovskite manganite at room temperature. Issue 18 (25th April 2016) - Singh, Brajendra
Abstract : Colossal magnetoimpedance, MI > +120%, was observed at room temperature for Ru = 0.3 composition in La0.7 Ca0.3 Mn1− x Ru x O3 due to the presence of Ru 4+, which otherwise was not significant for Ru = 0.1 and Ru = 0.2 compositions. Abstract : We have demonstrated Ru 4+ induced colossal magnetoimpedance (MI) at room temperature in a ∼1 Tesla magnetic field with a pulsed laser deposited La0.7 Ca0.3 Mn0.7 Ru0.3 O3 thin film. This composition showed a large negative ∼12% MI in the low frequency range (<5 MHz), a colossal positive MI > 120% in the intermediate frequency range (5 MHz to ∼13 MHz) and a negative MI in the high frequency range (∼13 MHz to 40 MHz) at room temperature. XAS data confirmed the predominant Ru valence state was 4+ in La0.7 Ca0.3 Mn0.7 Ru0.3 O3 . Ru 4+ induced (i) charge carrier localization and (ii) reduced hole carrier density enhances the MI in this composition, which otherwise was not significant in mixed valences Mn 3+ /Mn 4+ containing La0.7 Ca0.3 MnO3 and Ru 4+ /Ru 5+ and Mn 3+ /Mn 4+ mixed valences containing Ru = 0.1 and Ru = 0.2 compositions in La0.7 Ca0.3 Mn1− x Ru x O3 (0 ≤ x ≤ 0.3) thin films.